2021 European Conference on Optical Communication (ECOC) 2021
DOI: 10.1109/ecoc52684.2021.9605972
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-fiber Digital Predistortion Using Reinforcement Learning

Abstract: We demonstrate, for the first time, experimental over-the-fiber training of transmitter neural networks (NNs) using reinforcement learning. Optical back-to-back training of a novel NN-based digital predistorter outperforms arcsine-based predistortion with up to 60% bit-error-rate reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The hardware impairments considered in this paper are restricted to the IQM nonlinearity and the limited ENOB of the DAC, while the PA is assumed to be linear, as the PA nonlinearity is negligible when compared to that of the MZM. However, it should be noted that the proposed approach can be readily applied to a more general setup where the other transmitter components are not idealized (e.g., nonlinear PA and bandwidth-limited DAC (see our previous work [50]).…”
Section: Numerical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hardware impairments considered in this paper are restricted to the IQM nonlinearity and the limited ENOB of the DAC, while the PA is assumed to be linear, as the PA nonlinearity is negligible when compared to that of the MZM. However, it should be noted that the proposed approach can be readily applied to a more general setup where the other transmitter components are not idealized (e.g., nonlinear PA and bandwidth-limited DAC (see our previous work [50]).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In this paper however, we only focus on training of the PS filter, for which memory effects need to be taken into account. For the optimization of the mapper (i.e., NN1) or the DPD (i.e., NN3), we refer the reader to [23], [34] and our recent paper [50]. To that end, the parameters of the mapper, the DPD, and the demapper (i.e., NN4) are assumed to be pretrained and fixed during the PS filter training.…”
Section: Learning Without a Channel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To alleviate the impact of spectrum deformation by pre-equalization at Tx and post-equalization at Rx, many studies based on ML have been reported [55][56][57][58][59][60][61]. The recurrent neural network (RNN), which is used for learning timedependent patterns or time-dispersive patterns including inter-symbol interference, can be widely used for pre-/postequalization because RNN structure is similar to that of conventional digital FIR filters.…”
Section: Digital Signal Processing Based On MLmentioning
confidence: 99%
“…Such a requirement brings special challenges for experimental systems where no gradient can be calculated. Nevertheless, methods such as gradient-free optimizers 49 or reinforcement learning 52 show great promise to address the challenge.…”
Section: End-to-end Learning Of Phase-noise Robust Communicationmentioning
confidence: 99%